2013
DOI: 10.1111/dsu.12045
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type of Reconstruction After Mohs Micrographic Surgery and Surgeon-, Patient-, and Tumor-Specific Features: A Cross-Sectional Study

Abstract: Most post-Mohs closures are linear repairs, with more bilayered linear repairs more likely at certain anatomic sites and after a larger number of stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…We have found that the use of grafts and second intention techniques is more common in the SCC group, which is consistent with some studies that found that the techniques of closure most often used for reconstructing MMS defects are linear closures 32 and flaps. 1,33 However, these studies do not distinguish between BCC and SCC reconstruction.…”
Section: Discussionsupporting
confidence: 91%
“…We have found that the use of grafts and second intention techniques is more common in the SCC group, which is consistent with some studies that found that the techniques of closure most often used for reconstructing MMS defects are linear closures 32 and flaps. 1,33 However, these studies do not distinguish between BCC and SCC reconstruction.…”
Section: Discussionsupporting
confidence: 91%
“…Most Mohs defects were closed by primary suturing in this study and that of Alam et al . [ 45 ] Flaps and grafts were seen increasingly after more than two Mohs stages. [ 45 ] This was the same in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is also to look like a face [37]. Physical attractiveness positively correlates with social success and directly impacts how a person is treated [38][39][40]. While a small flap closure is technically straightforward, a large nasal reconstruction with a forehead flap, cartilage grafting, and nasal lining reconstruction is more complex and comprised of a large number of steps that all need to be completed flawlessly.…”
Section: When Reconstruction Cannot Be Completed By Dermatologist Promentioning
confidence: 99%